Historicizing Injustice: The Museum of Memory and Human Rights, Santiago, Chile. (June 2015) - Opotow, Susan; Hunter, Andrea G.; Stewart, Abigail J.
<x xml:space="preserve">Abstract</x> Focusing on the Museum of Memory and Human Rights in Chile, this article examines the intersection of psychology and history as they bear on conflict, memory, and justice. The museum commemorates victims of mass detentions, disappearances, and human rights violations during the Pinochet dictatorship (1973–1990). This article discusses historical precursors to the coup, including United States involvement in Chilean politics. Utilizing the construct, scope of justice, it discusses representations of moral exclusion and moral inclusion in the museum's exhibition. Museum professionals who developed the exhibition describe the challenges of their work because opposing political perspectives about the dictatorship persist. The article suggests that historical museums on injustice can serve as sites that engage such clashing viewpoints. Surfacing narratives and counternarratives about the past and airing tensions and haunting questions can offer insight into social issues, policies, and conflicts that persist today.